Uma análise da atividade comercial entre o município de São Gonçalo do Amarante e os demais municípios cearenses: uma aplicação do modelo gravitacional - Holanda Filho, José Edson (2017)
The dynamics of international and regional trade have stimulated further studies and research around the many factors that influence the way in which multilateral negotiations take place. This understanding of both the volume and the qualitative aspects that impact and determine commercial transactions is of the utmost importance for the formulation of a country's external and internal public policies, especially when it is perceived that commercial growth is fundamental for the development of a country. This work applied the gravitational model in order to measure the main factors that interfere in the existing commercial pattern between the Municipality of São Gonçalo do Amarante and the other municipalities of Ceará, based on data on the flow of goods and goods from the NF-e System Of SEFAZ / CE. For that, we used panel data from the 183 municipalities of the State of Ceará for the years 2011 to 2014, in a log-linear specification that contemplates the traditional variables of the already consolidated empirical studies (GDP and distance), in addition to dummies which portray characteristics geographies (adjacencies) and economic (Regional Frontier Effect - Metropolitan Region of Fortaleza), whose parameters were estimated through the Ordinary Least Squares Method. The results found, in a general way, are adequate to the hypothesis of the gravitational model at the intermunicipal level: that trade between two entities is positively determined by attraction factors, such as GDP, but negatively impacted by resistance factors, such as distance.